Turkey-EU Customs Union: Its Modernization and Potential for Turkey-EU Relations - Nas, Cigdem (SETA FOUNDATION, 2018)
The customs union is still one of the most concrete outcomes of Turkey's gradual integration to the EU. However, due to changes in world trade, EU trade policy and Turkey-EU relations, the customs union is in need of a comprehensive revision and update. This commentary aims to analyze the current working and need for upgrading of the customs union within the overall scope of Turkey and EU relations. It is argued that the customs union is not only about the bilateral trade relationship, and its modernization could bring a breath of fresh air to Turkey-EU relations and reignite the process of Turkey's gradual integration into the EU.
Keywords: Government & Law